342 Cardiorespiratory fitness and systemic vascular resistance: oxygen pressure as a novel marker of peripheral vascular response during cardiopulmonary exercise testing. (8th December 2021) - Centorbi, Claudio Stefano; Lazzeroni, Davide; Moderato, Luca; Bini, Matteo; Brambilla, Lorenzo; Brambilla, Valerio; Camaiora, Umberto; Geroldi, Simone; Meloni, Luigi; Coruzzi, Paolo; Piepoli, Massimo; Ardissino, Diego; et al.
Abstract: Aims: The key role of systemic vascular resistance (SVR) in cardiovascular performance during exercise has been invasively demonstrated, however no data have been non-invasively obtained by analysing SVR response using cardiopulmonary exercise testing (CPET). To investigate the relationship between SVR at peak, maximum oxygen uptake (VO2 peak), and its determinants using CPET. Methods and results: 1130 consecutive subjects were enrolled; according to physiology, SVR was determined as the ratio between mean arterial pressure (MAP) and cardiac output (CO). A novel parameter, named oxygen pressure (MAP peak/VO2 peak) was also created. Mean age was 61 ± 12 years and male gender was prevalent (61%); 66% of patients had arterial hypertension, 74% dyslipidaemia, 19% diabetes, 20% had smoking habit, and 26% previous history of cardiovascular (CV) disease. Significant inverse correlations between SVR peak and VO2 /kg peak ( P < 0.001), oxygen pulse ( P < 0.001), CV efficiency ( P < 0.001), chronotropic response ( P < 0.001), and oxygen uptake exaction slope ( P < 0.001) were found. Moreover, positive correlation between SVR peak and VE/VCO2 slope ( P < 0.001) was observed. After multivariate analysis, the inverse correlation between peak SVR and peak VO2 remained significant ( P < 0.001). Similar results were found considering oxygen pressure. Conclusions: Low values of SVR at peak exercise, non-invasively evaluated with CPET, are associated with high levels of cardiorespiratory fitness. Oxygen pressure may represent a novel and simple CPET marker of peripheral vascular response to exercise, thereby representing a promising field of research in exercise medicine.